2017
DOI: 10.3389/fmicb.2017.01854
|View full text |Cite|
|
Sign up to set email alerts
|

Human Cytomegalovirus IE2 86 kDa Protein Induces STING Degradation and Inhibits cGAMP-Mediated IFN-β Induction

Abstract: Stimulator of interferon genes (STING) is a critical signaling molecule in the innate immune response against DNA viruses by either directly sensing intracellular DNA or functioning as an adaptor molecule to activate the type I interferon (IFN) signaling pathway. We determined the functional interaction between STING and human cytomegalovirus (HCMV). A cDNA library containing 133 HCMV ORFs was screened to identify viral genes that inhibit STING-induced IFN-β promoter activation. Among the screened ORFs, UL122,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 50 publications
1
34
0
Order By: Relevance
“…While some herpesviral antagonists target cGAS directly Zhang et al, 2016;Su & Zheng, 2017), others mediate the degradation of STING (Kim et al, 2017) or target downstream signaling pathways (Christensen et al, 2016). While some herpesviral antagonists target cGAS directly Zhang et al, 2016;Su & Zheng, 2017), others mediate the degradation of STING (Kim et al, 2017) or target downstream signaling pathways (Christensen et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While some herpesviral antagonists target cGAS directly Zhang et al, 2016;Su & Zheng, 2017), others mediate the degradation of STING (Kim et al, 2017) or target downstream signaling pathways (Christensen et al, 2016). While some herpesviral antagonists target cGAS directly Zhang et al, 2016;Su & Zheng, 2017), others mediate the degradation of STING (Kim et al, 2017) or target downstream signaling pathways (Christensen et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The cGAS-STING signaling pathway plays a pivotal role in the antiviral innate immune response with the number of corresponding viral antagonists rising steadily. While some herpesviral antagonists target cGAS directly Zhang et al, 2016;Su & Zheng, 2017), others mediate the degradation of STING (Kim et al, 2017) or target downstream signaling pathways (Christensen et al, 2016). However, the m152 protein is a clear stand out: It modulates this pathway differentially by antagonizing cGAS-STING-mediated activation of type I IFN signaling, while leaving cGAS-STING-mediated activation of NF-jB signaling intact, and it does so by delaying trafficking of STING from the ER to the Golgi compartment (Fig 9).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to degradation of cGAS, DENV and other related flaviviruses proteolytically cleave STING using the viral protease complex NS2B3, blocking induction of signaling [45,46 ]. In addition, the HCMV IE86 protein promotes STING degradation in the proteasome, restricting activation of downstream signaling [47].…”
Section: Pathogens Block Sting Signalosome Assemblymentioning
confidence: 99%
“…Moreover, the HCMV immediate early (IE) 86 kDa protein (IE86), negatively affects IFN-β mRNA transcription by preventing NF-κB binding to the IFN-β promoter (Taylor and Bresnahan, 2006). Intriguingly, a recent study by Kim et al (2017) has shown that IE86 downregulates STING protein, suggesting that IE86 may also target STING for proteasomal degradation. Interestingly, STING levels were restored upon treatment with the peptide aldehyde MG132, which prevents the proteolytic activity of the proteasome complex.…”
Section: The Ifn System and Hcmv: A Stormy Relationshipmentioning
confidence: 99%